Clinical findings on chromosome 1 copy number variations - Filipa Batista Ferreira Leitão (2021)
Copy number variants (CNVs) are a major contribution to genome variability, and the presence of CNVs on chromosome 1 is a known cause of morbidity. The main objective of this study was to contribute for chromosome 1 disease map, through the analysis of patients with chromosome 1 CNVs. A cross-sectional study was performed using the array comparative genomic hybridization (array-CGH) database of the Genetic Department of the Faculty of Medicine. Patients with pathogenic (P) or probably pathogenic (VOUS-PP) CNVs on chromosome 1 were selected for the study. Clinical information was collected for all patients. Databases and related literature were used for genotype-phenotype correlation. From a total of 2516 patients included in the database we identified 24 patients (0.95%) with P (9 patients) or VOUS-PP (15 patients) CNVs on chromosome 1. These CNVs account for 6.1% (24/392 CNVs) of the total P/VOUS-PP CNVs in the database. Most common CNVs found were on 1q21.1-1q21.2 region. This study reinforces the association between chromosome 1 CNVs and neurodevelopmental disorders and craniofacial dysmorphisms. Additionally, it also strengthened the idea that CNVs interpretation is not always a linear task due to the broad spectrum of variants that can be identified between benign and clearly pathogenic CNVs.